Innovation Management Arabic Language Learning Based on Multimedia Audio Visual Animation Increase Learning Class VIII MTs N 4 North Padang Lawas - Siregar, Nur Milan; Siregar, Nidaul Hasanah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Animated audio-visual media is a learning media that can help increase the interest in learning  students of Class VIII MTs. N 4 North Padang Lawas in following the teaching and learning process in the classroom.  Eliminate the saturation of student learning, especially in Arabic subjects who have only used classical learning methods such as: lecture methods.  Therefore, this animation media can display audio visual animation learning in Arabic not only for entertainment alone for students. This media can also provide information about Arabic language learning and display animated videos containing Arabic learning in accordance with grade VIII student level material.  Making this animaton media using the plotagon application, the creation of this animation media has been explained in chapter two and the image in in the documentatio setion. This research uses a type of qualitative research with an experimental approach and ADDIE research and development which must produce a product in learning. There are stages of research carried out as follows: 1) stages of analysis, 2) stages of design, 3) stages of development, 4) stages of implementation, 5) stages of evaluation. Research has been assessed by validators who are active in digital learning media.